359 Mortality trends in gynecological cancers in Chile. (13th November 2020) - Brañes, J; Jensen, R; Vera, C; Donoso, E
Abstract : Introduction: Gynecologic cancers account for an important number of deaths in women in Chile. Substantial efforts have been made over the last 20 years to improve access to health care to reduce cancer mortality. Objective: To evaluate gynecologic cancer mortality trends during the last 21 years in Chile. Methods: Cause-of-death figures were obtained from 1996 until 2017. Age-adjusted mortality rate was calculated for each gynecologic cancer, using the 2017 census data as the standard population. Logistic regression model was utilized to determine trends, confidence interval and reveal changes in tendencies if occurred. Results: Three of the four studied cancers showed a significantly reduction in mortality rates. There was a sustained reduction, although modest, in breast and ovarian cancer mortality of 0.77% (CI -1.0 to -0.6) and 0, 63% (CI -1.1 to -0.2) per year, respectively. The most significant change was observed in cervical cancer with an annual reduction of 4% (CI -4.3 to -3.7). All corpus uteri cancers considered together, had a non-significant tendency towards reduction. In a subanalysis of mortality for cervical cancer in women under 40 years, we observed a break in the negative tendency after 2011, revealing a rise of 5.1% (CI -0.6 to 11.2) per year. Conclusion: There was a reduction in mortality rate in most of the studied cancers. Although cervical cancer showed the most important reduction trend, is still far from the lowest figures published in the literature. The change in tendency for the younger population with cervical cancer is of concern.